La búsqueda del lector híbrido como motivo implícito de la traducción pragmática. Caso de la novela Puppet de Margarita Cota-Cárdenas y su traducción al inglés - Kasperska, Iwona (Studia Romanica Posnaniensia, 2021)
The article deals with a particular case of intra- and intertextual translation of a highly pragmatic nature, which can be seen in Puppet. A Chicano novella by Margarita Cota-Cárdenas. Composed mainly of fragments of conversations, monologues and personal letters, the novel reflects Spanish-English codeswitching, as a characteristic feature of the speech of the Mexican American community in the USA. By (re)producing a range of heteroglossal forms of this community communication, Cota-Cárdenas uses translation procedures to reach the hybrid reader who is, at the same time, the hallmark of Chicanos. The multilingual strategies (Hansen Esplin, 2012) of the author and the translators, Barbara D. Riess and Tino Sandoval, become the main pragmatic objective of the novel, both in its source and target versions. Given the multitude of translation procedures observed in both versions of this hybrid novel, the relativity of traditional translation terms, such as original and translation, is also discussed, as both turn out to be bilingual texts and pragmatic translations.